Fuzzy LPCM controlled buck integrated PFC convert-er for Class-C&D appliances - Subbarao, Mopidevi; SaiBabu, Ch.; Satyanarayana, S. (International Journal of Engineering and Technology, 2018)
This propounded a novel method of design and implementation of a fuzzy linear peak current mode (LPCM) controlled Buck Integrated Power Factor Correction (PFC) Converter. It derives its advantages through low buck capacitor voltage and single control switch, which leads to reduced complex control and price. Sub-harmonic oscillations generates in peak current controller can be nullified by using ramp signal, there by improves the overall performance of the converter. The fuzzy controller (FLC) robust and effective than conventional linear controllers like P, PI, PID, hence in this work a (90 – 265V), 50Hz AC, 48V DC and 100 kHz frequency converter is implemented in MATLAB/Simulink software and results are verified experimentally. Results show that converter meets international regularity commission regulations.